Adaptation and psychometric properties of the Sense of Coherence Scale (SOC-29) in young university students - Torres Tapia, Neftali (2023)
Objective: to adapt and analyze the psychometric properties of the Sense of Coherence Scale (SOC- 29). Methodology: the research is classified as a psychometric instrumental study, non-experimental, cross-sectional design, quantitative approach and non-probabilistic sampling. The study population consists of 500 university students to whom the survey was conducted virtually. The instrument     has 15 items distributed in 3 dimensions: understandability, manageability and significance, with a dichotomous response type. To analyze the validity of the content, the expert judgment criteria were applied, with the collaboration of 8 judges who evaluated the clarity, context, congruence and mastery of the construct. Results: an Aiken V index V= 0.91 was obtained, an internal consistency by total Cronbach's alpha of 0.702, which shows that the instrument is reliable. The confirmatory factorial analysis resulted in a measure of KMO= 0.779 and a Sig value < 0.00, the total variance explained by 3 factors achieved an accumulated percentage of 42.1%, the factorial loads are greater than .3 distributed in three components, concludes that item 11 should be eliminated, since it improves the reliability level by Cronbach’s alpha. Conclusion: the questionnaire has adequate psychometric properties such in validity